2019
DOI: 10.1186/s12913-019-3883-x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to develop collectivistic leadership in healthcare settings: a systematic review

Abstract: BackgroundCollective or shared leadership approaches have been associated with team performance outcomes in several sectors. Based on this evidence, there have been calls for more inclusive approaches to leadership in healthcare settings, but guidance on how to achieve collective leadership is lacking. This study synthesised knowledge of interventions to introduce collectivistic leadership in healthcare settings.MethodsThe databases of PubMed, PsychInfo, ABI Inform, Cochrane and CINAHL and three grey literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 53 publications
2
87
0
2
Order By: Relevance
“…Collective leadership has been documented to be effective at achieving meaningful change at the healthcare provision level and in developing policies where there are multiple stakeholders. 16,17 Our research also highlights the role of differing types of organizations, and their centrality to the delivery of assistive technology. We were interested to see that International NGOs, while playing a critical role in the funding and delivery of assistive technology, are not as central to the network as those organizations which represent people with disabilities, service delivery organizations, and ministries.…”
Section: Discussionmentioning
confidence: 83%
“…Collective leadership has been documented to be effective at achieving meaningful change at the healthcare provision level and in developing policies where there are multiple stakeholders. 16,17 Our research also highlights the role of differing types of organizations, and their centrality to the delivery of assistive technology. We were interested to see that International NGOs, while playing a critical role in the funding and delivery of assistive technology, are not as central to the network as those organizations which represent people with disabilities, service delivery organizations, and ministries.…”
Section: Discussionmentioning
confidence: 83%
“…While collective leadership is not a panacea to solve the wicked problems inherent in healthcare settings, and there are inevitably occasions that require a more hierarchical leadership approach [60], the evidence strongly suggests that collective leadership interventions can promote more effective teamworking, enhance quality of care and patient safety and improve staff and patient satisfaction [13]. This study has gone beyond the question of effectiveness by interrogating the causal and generative mechanisms that result in the outcomes observed when collective leadership is practiced.…”
Section: Discussionmentioning
confidence: 97%
“…A realist synthesis of the literature was conducted on studies retrieved during a systematic review of interventions to develop collective leadership in healthcare settings (full search strategy available in published paper) [13]. Twenty-one papers were assessed for rigour and ability to add to the developing programme theory and 19 were included in the final analysis (two were excluded due to insufficient information to inform IPT).…”
Section: Realist Synthesis Of the Extant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Collective and shared approaches to leadership have been found to enhance team effectiveness and team performance outcomes ( D’Innocenzo et al , 2016 ; Wang et al , 2014 ). There is now considerable evidence for the effectiveness of collective leadership interventions in healthcare settings ( De Brún et al , 2019 ). These studies have indicated the positive impact of collective leadership interventions on staff engagement, quality improvement, team-working and patient satisfaction ( De Brún et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%